Controversial Phenomenon of The Freedom to Buy and Sell Contraceptives in Palangka Raya - Ajeng Hijriatul Aulia; Ibnu Elmi A. S Pelu; Nyimas Tasya Farhana; Muhammad Luthfi Setiarno Putera (Indonesian Journal of Law and Islamic Law (IJLIL), 2025)
This study examines the controversial phenomenon of the freedom to buy and sell contraceptives in Palangka Raya, which is linked to the impact of unrestricted contraceptive distribution policies on vulnerable groups, particularly adolescents. According to data from the Central Statistics Agency (BPS) in 2021, Central Kalimantan has a relatively high early marriage rate, which has contributed to an increase in pregnancies at young ages. In this context, the researcher criticizes Nur Fadlan’s view in his study arguing that the sale of contraceptives should not be restricted based on age or marital status, providing the sales agreement meets the conditions and pillars of sharia law. This opinion is considered to be in contradiction with the realities on the ground, where the freedom to access contraceptives, especially among adolescents who are not physically or mentally ready, can lead to negative consequences such as unwanted pregnancies and other health risks. Therefore, the researcher argues that the unrestricted sale of contraceptives without age or marital status limitations needs to be reconsidered. This study recommends updating policies to be more selective and protective, such as implementing age restrictions and requiring guidance from healthcare professionals during the contraceptive distribution process, to protect adolescents’ health and well-being. Strengthening oversight of contraceptive distribution should also be carried out in accordance with the provisions of Article 31 Paragraph (1) of Government Regulation Number 87 of 2014 to ensure the policy effectiveness in protecting younger generations from potential health risks.